High-resolution XRF analysis of a sediment core IZN19-03 from Lake Iznik (NW Turkey) - Gastineau, Renaldo; De Sigoyer, Julia; Sabatier, Pierre; Fabbri, Stefano C; Anselmetti, Flavio S; Develle, Anne-Lise; Şahin, Mustafa; Gündüz, Serkan; Niessen, Frank; Gebhardt, Andrea Catalina (PANGAEA, 2020)
The relative contents of major and trace elements were analyzed in 2019 with an X-Ray Fluorescence (XRF) at 1-mm resolution on the surface of each sediment core with an Avaatech Core Scanner (EDYTEM Laboratory). The split-core surface was first covered with a 4-μm-thick Ultralene film to avoid contamination and desiccation of the sediment. Element intensities are expressed in counts per second (cps). Different settings were used with 10 kV and 0.2 mA during 15 s to detect Al, Si, S, K, Ca, Ti and at 30 kV and 0.3 mA during 20 s for Mn, Fe, Ni, Cu, Zn, Br, Rb, Sr, Zr, Pb (Richter et al., 2006; doi:10.1144/GSL.SP.2006.267.01.03).
Keywords: Iznik; Lake; sediment analysis; Turkey; XRF